2021
DOI: 10.1055/a-1347-2550
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Continuous Glucose Monitoring Systems May Affect Metrics: Clinically Relevant Differences in Times in Ranges

Abstract: Background Continuous glucose monitoring-derived parameters are becoming increasingly important in the treatment of people with diabetes. The aim of this study was to assess whether these parameters, as calculated from different continuous glucose monitoring systems worn in parallel, are comparable. In addition, clinical relevance of differences was investigated. Methods A total of 24 subjects wore a FreeStyle Libre (A) and a Dexcom G5 (B) sensor in parallel for 7 days. Mean glucose, coefficient of variation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Because people with T1D did not change their type of CGM device, the choice of the CGM system did not affect glucometrics. This is important to note because it is well known that Freestyle Libre reports a higher proportion of TBR, which might impact therapy recommendations 39 . Also, subjects had to be using the same basal insulin throughout the study.…”
Section: Discussionmentioning
confidence: 99%
“…Because people with T1D did not change their type of CGM device, the choice of the CGM system did not affect glucometrics. This is important to note because it is well known that Freestyle Libre reports a higher proportion of TBR, which might impact therapy recommendations 39 . Also, subjects had to be using the same basal insulin throughout the study.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, the FreeStyle Libre sensor algorithm was updated in 2020, with superior MARD of 9.2% in adults, based on 18,926 paired observations. 4 The updated algorithm also invalidates the conclusions reported by Freckmann et al 2 Concurrence data for the earlier generation algorithm indicated that FreeStyle Libre sensors had a low rate of readings in the euglycemic range when reference blood glucose was in the hypoglycemic range, 5 and that it was more common that a low-glucose sensor reading would prompt safe and timely action when blood glucose was still euglycemic. This would explain the data presented by Freckmann et al In contrast, the latest FreeStyle Libre sensor algorithm has improved performance across all glucose ranges, 4 such that 98.4% of FreeStyle Libre sensor readings <70 mg/dL are within ± 20 mg/dl of paired blood-glucose reference values and 95% of readings >180 mg/dL are within ± 20% of reference values.…”
mentioning
confidence: 75%
“…In addition, the heterogenous profile of our patients avoided subgroups analysis to better understand the factors explaining amplitude's difference of the benefits. Improvements on glycemic management by switching from a system to another one depend also on the accuracy of IG values, attested by the MARD (mean absolute relative difference), which changes according to the device considered, rapid glycemic fluctuations, the skin sensor location, the lifespan of the sensor, or even the repeated use of some drugs [23][24][25][26][27], that was not further studied. No standardized questionnaires were retrieved in the medical folders for evaluating satisfaction and quality of life or the evolution of the feeling and fear of hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%